Optimizing Guidance and Counseling by the Drug Investigation Unit in Preventing Narcotics Abuse Among Adolescents in the Denpasar Police Area - Komang Andhika Haditya Prabu (Police Studies Review, 2021)
This research is motivated by the increase in unemployment in Indonesia due to the prolonged Covid-19 pandemic, which has led to an increase in narcotics abuse cases among teenagers in the Denpasar Polresta area. The existence of the Covid-19 health protocol causes the Denpasar Police Narcotics Unit to be unable to take preemptive steps in the form of narcotics guidance and counseling in 2020. This study aims to identify and analyze what efforts can be made by the Denpasar Police Narcotics Unit to optimize narcotics guidance and counseling activities as well as identify and analyze factors that influence the guidance and counseling of narcotics. This study uses a qualitative approach with the method of field and file research. This study uses primary and secondary data sources, and takes place in Denpasar City. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Data collection techniques used interview, observation, and document studies. The concepts used in this study are the concepts of Optimization, Guidance and Counseling, Prevention, Narcotics, Narcotics Abuse, and Adolescents, while the theories used are Crime Prevention Theory, The Six "M" in Management, and Media Dependency Theory. The results showed that 1) the Denpasar Police Narcotics Unit had not yet found a solution or alternative to optimize narcotics guidance and counseling activities due to the Covid-19 pandemic; 2) The factors that influence the guidance and counseling on narcotics are influenced by 8 factors consisting of internal and external factors, and 5 of the 8 factors that have a negative effect. Based on the Media Dependency theory, the use of online application media and social media can be a solution to the non-implementation of narcotics guidance and counseling.